Out-of-hospital cardiac arrest and ambient air pollution: a dose-effect relationship and a predictive role in OHCA risk. (14th October 2021) - Gentile, F R; Primi, R; Baldi, E; Compagnoni, S; Mare, C; Contri, E; Reali, F; Bussi, D; Facchin, F; Currao, A; Bendotti, S; Savastano, S
Abstract: Background: Pollution has been suggested as a precipitating factor for cardiovascular diseases via a series of different mechanisms. However, data about the link between the different air pollutants and the risk of out-of-hospital cardiac arrest (OHCA) are limited and controversial. Purpose: The primary aim of this study is to examine the impact of short-term exposure to particulate and gaseous pollutants on the incidence of OHCA in a vast metropolitan and rural area that encompasses four provinces of the Po Valley in Northern Italy, one of the most polluted areas in Italy and Europe due to its levels of industrialization and high population density. The secondary aim of this study is to look for a dose-effect curve, which could help predict OHCA incidence based on the concentration of pollutants in a specific area. Methods: This is a retrospective analysis of prospectively collected data both in the OHCA registry (Lombardia CARe) and in the database of the regional agency for environmental protection (ARPA) of the Lombardy region. All medical OHCAs and the mean daily concentration of pollutants including fine particulate matter (PM10, PM2.5), benzene (C6H6), carbon monoxide (CO), nitrogen dioxide (NO2), sulphur dioxide (SO2) and ozone (O3) were considered from January 1st to December 31st, 2019 in the southern part of the Lombardy region (provinces of Pavia, Lodi, Cremona and Mantua; 7863 km 2 ; about 155ehab724.2654 inhabitants). Days were divided into high or low incidence of OHCA according to the median daily incidence. A Probit dose-response analysis and both uni- and multivariable logistic regression models were provided for each pollutant. Results: The median daily incidence of OHCA was 0.3 cases/100, 000 inhabitants. Benzene was the pollutant with the greatest difference between days at high and low incidence of OHCA [0.7 (IQR 0.4–1.2) vs 0.4 (IQR 0.3–0.7), p<0.001], whereas SO2 had the lowest and least significant difference between the two periods [3.2 (IQR 2.8–3.6) vs 3.1 (IQR 2.7–3.5), p=0.046]. O3 showed a countertrend, being significantly higher in the low-incidence period [29.9 (IQR 10.9–61.7) vs 56.1 (IQR 25.5–74.1), p<0.001] as well as temperature [10.1— (IQR 5.2–14.8) vs 15.1 (IQR 8.9–23.3), p<0.001]. By using the Probit regression analysis and after adjusting for temperature, a dose-response relationship was demonstrated for all the tested pollutants. Conclusions: Our results clarify the link between pollutants and the acute risk of cardiac arrest suggesting the need of both improving the air quality and integrating pollution data in future models. FUNDunding Acknowledgement: Type of funding sources: None.